Analysis of the Production and Development of Etawah-grade (Peranakan etawah, PE) Dairy Goats on Post-sand-mining Land in Sumedang Regency, West Java - Fuah, A.M.; Baihaqi, M.; Priyanto, R.; Yamin, M.; Lucia, C.N.S.D.; Panca, D.M.H.K.S (Pakistan Journal of Nutrition, 2017)
Background and Objective: Problems arising from sand mining include very low soil fertility, erosion and a lack of water resources. Reclamation to improve this mined land can initially involve recontouring, regrading, resloping and revegetation. Reclamation success, especially revegetation with plants suitable for forage, can be followed by integration with livestock. The aim of this study was to identify and analyze the production capacity and potential of dairy goat farms developed on post-sand-mining land in Sumedang Regency, West Java. Materials and Methods: Surveys and group discussions were performed to obtain information about farming practices and management. Secondary data were derived from the literature, reports and relevant institutions and in-depth discussions with experts were carried out as part of a detailed analysis of existing production systems. An Analytical Hierarchy Process (AHP) analysis and external (EFAS) and internal (IFAS) factor analysis strategies were used to determine the dominant factors influencing PE dairy goat production and to formulate appropriate strategies for sustainable production in post-sand-mining areas. Results: The results indicated a high percentage (75%) of productive females with low mating ratios 1:3-1:5. From an economic point of view, the Revenue-to-Cost (R/C) ratio was 1.57. An internal-external matrix analysis showed that growth and stability strategies should be implemented and a space matrix analysis indicated that a diversification strategy should be applied. Conclusion: Finally, an integrated approach, through improving the capacity of farmer’s groups and support from local government will help to improve sustainable PE dairy goat production and provide benefits to small farmers on post-sand-mining land.